Additive for fluid catalytic cracking catalysts, method for producing the same, additive mixture including the additive, and fluid catalytic cracking catalyst composition including the additive mixture

JP2023156821A5Active Publication Date: 2025-04-18JGC CATALYSTS & CHEMICALS LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022066413
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-04-13
Publication Date
2025-04-18
Estimated Expiration
2042-04-13

AI Technical Summary

Technical Problem

Conventional FCC catalyst additives face challenges in maintaining high yields of lower olefins like propylene throughout the cracking process, particularly when dealing with feedstock hydrocarbon oils containing heavy metals, and suffer from deteriorating catalytic activity over time.

Method used

A fluid catalytic cracking catalyst additive composed of pentasil-type zeolite and an inorganic oxide matrix containing two types of phosphorus compounds, with specific molar ratios and properties, is developed to enhance yield and stability, including a production method involving slurry preparation, spray drying, and heat treatment.

Benefits of technology

The additive maintains high yields of lower olefins such as propylene from the beginning to the end of the cracking process, even with heavy metals present, and exhibits improved wear resistance and hydrothermal stability.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide an additive for fluid catalytic cracking catalysts that can yield lower olefins such as propylene in high yield from the start to the end of the treatment process of raw material hydrocarbon oil, and a method for producing the same.SOLUTION: An additive for fluid catalytic cracking catalysts includes a pentasil-type zeolite and an inorganic oxide matrix component including two phosphorus compounds. In the additive for fluid catalytic cracking catalysts, the pentasil-type zeolite content is 25-60 mass%. For the ratio of the phosphorus content to the alumina content in the additive for fluid catalytic cracking catalysts, the molar ratio of P2O5 / Al2O3 is 0.30-0.53 when the phosphorus content is expressed in terms of P2O5. The molar ratio of the silicon dioxide content to the alumina content in the pentasil-type zeolite, SiO2 / Al2O3, is 25-40. The wear resistance index (CAI) is 20 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to an additive for a fluid catalytic cracking catalyst, a method for producing the additive, a mixed additive containing the additive, and a fluid catalytic cracking catalyst composition containing the mixed additive. More specifically, the present invention relates to an additive used together with a fluid catalytic cracking catalyst (hereinafter also referred to as an "FCC catalyst") to increase the octane number of gasoline and increase the production of light olefins in the fluid catalytic cracking (hereinafter also referred to as "FCC") of a hydrocarbon feedstock oil, and a method for producing the additive. [Background technology]

[0002] The main purpose of a fluid catalytic cracking unit (hereinafter also referred to as "FCC unit") in an oil refinery is to catalytically crack a hydrocarbon feedstock to produce a gasoline fraction. The gasoline fraction obtained by catalytically cracking the hydrocarbon feedstock is desired to have a high octane number. Some oil refineries are required to use an FCC unit to catalytically crack a hydrocarbon feedstock to produce a gasoline fraction, while at the same time increasing the production of lower olefins such as ethylene, propylene, and butene, which are petrochemical feedstocks.

[0003] In order to meet this demand, various methods have been proposed for carrying out FCC by adding a composition containing a pentasil type zeolite such as ZSM-5 type zeolite (hereinafter also referred to as an "additive catalyst") as an additive for the FCC catalyst to the catalyst used for FCC.

[0004] As such additives, for example, Patent Document 1 discloses a composition comprising a pentasil-type zeolite and an inorganic oxide matrix, which has many macropores with pore diameters of approximately 100 nm. Patent Document 2 discloses a particle composition comprising a pentasil-type zeolite, a porous inorganic oxide, and phosphorus pentoxide, in which the surface portion of the particle contains more phosphorus pentoxide than the center portion. Patent Document 3 discloses an FCC catalyst additive that can increase the production of propylene and other products, and that contains a zeolite such as ZSM-5 zeolite, a phosphate, clay, and a binder containing silica. Furthermore, Patent Document 4 discloses an FCC catalyst additive that contains a modified ZSM-5 zeolite with specified properties, a filler, and a binder.

[0005] Patent Document 5 discloses a catalyst with excellent attrition resistance that contains a large amount of zeolite and also contains phosphorus and alumina, and that this catalyst can be added to a catalyst for use in the FCC process. Patent Document 6 discloses that the hydrothermal resistance of zeolite is improved by treating the zeolite with an aqueous solution containing phosphate ions. Patent Document 7 discloses an FCC catalyst containing zeolite, kaolin, a phosphorus compound, a high-density non-reactive component, and optionally reactive alumina, and that this catalyst is also suitable as an additive for cracking processes using large-pore molecular sieve components. Patent Document 8 discloses an additive for FCC catalysts that has a unique peak based on the results of P-NMR measurements. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Laid-Open No. 2005-270851 [Patent Document 2] Japanese Patent Application Laid-Open No. 2007-244964 [Patent Document 3] Special Publication No. 2014-527459 [Patent Document 4] International Publication No. 2017 / 82345 [Patent Document 5] Special Publication No. 2002-537976 [Patent Document 6] Japanese Patent Application Publication No. 04-200744 [Patent Document 7] Special Publication No. 2007-534485 [Patent Document 8] International Publication No. 2019 / 131381 [Non-patent literature]

[0007] [Non-Patent Document 1] Technical report magazine "Catalyst Chemical Technical Report" Vol.13, No.1, P65, 1966 Summary of the Invention [Problem to be solved by the invention]

[0008] However, conventional FCC catalyst additives have room for further improvement in terms of obtaining a high yield of lower olefins such as ethylene and propylene, since the feedstock hydrocarbon oil to be fluid catalytic cracked may contain a large amount of heavy metals. Conventional FCC catalyst additives have the problem of delaying the development of the catalytic activity of the FCC catalyst in the early stages of the fluid catalytic cracking process. Furthermore, conventional FCC catalyst additives have the disadvantage of deteriorating with use over a long period of time in the fluid catalytic cracking process. As a result, even when catalytic cracking of feedstock hydrocarbon oil is performed using conventional FCC catalyst additives, the yield of lower olefins is likely to decrease.

[0009] From this perspective, in a feedstock hydrocarbon oil treatment process using fluid catalytic cracking, it is useful in industrial processes to catalytically crack the feedstock hydrocarbon oil over a long period from the initial stage to the final stage to produce a gasoline fraction, while at the same time increasing the production of lower olefins such as ethylene, propylene, and butene, which are petrochemical feedstocks, and to continuously produce lower olefins at a high yield.

[0010] In view of these problems, the present invention aims to provide an additive for a fluid catalytic cracking catalyst, which is used together with a fluid catalytic cracking catalyst and enables production of lower olefins such as propylene in high yields from the initial to final stages of the treatment process of a feed hydrocarbon oil, and a method for producing the same. Another object of the present invention is to provide a mixed additive containing the additive for a fluid catalytic cracking catalyst, and a fluid catalytic cracking catalyst composition containing the mixed additive. [Means for solving the problem]

[0011] With this technical background in mind, the inventors have conducted extensive research to solve the above-mentioned problems, and as a result have discovered that a specific additive for a fluid catalytic cracking catalyst containing a pentasil-type zeolite and an inorganic oxide matrix component containing two types of phosphorus compounds can be used to obtain lower olefins such as propylene in high yields from the initial to final stages of the treatment process of a feed hydrocarbon oil, and have thus developed the present invention.

[0012] The gist of the present invention, which has been developed to solve the above problems and achieve the above objects, is as follows. [1] An additive for a fluid catalytic cracking catalyst comprising a pentasil-type zeolite and an inorganic oxide matrix component containing two types of phosphorus compounds, wherein the additive contains 25 to 60 mass% of the pentasil-type zeolite, the phosphorus content relative to the alumina contained in the additive is a molar ratio of P2O5 / Al2O3 of 0.30 to 0.53 when the phosphorus component is converted into P2O5, the molar ratio of SiO2 / Al2O3, which is the silicon dioxide content relative to the alumina contained in the pentasil-type zeolite, is 25 to 40, and the additive has an attrition resistance index (CAI) of 20 or less. [2] A method for producing an additive for a fluid catalytic cracking catalyst, comprising a pentasil-type zeolite and an inorganic oxide matrix component containing two phosphorus compounds, the method comprising: Step a: obtaining a mixed slurry containing a pentasil-type zeolite and an inorganic oxide matrix component containing two kinds of phosphorus compounds; Step b: spray-drying the mixed slurry to obtain a dry additive; and step c: heat-treating the dried additive to obtain an additive for a fluid catalytic cracking catalyst. [3] A mixed additive for a fluid catalytic cracking catalyst, comprising additive A and additive B, The additive A is the additive for a fluid catalytic cracking catalyst according to claim 1, The additive B comprises a ZSM-5 type zeolite and an inorganic oxide matrix component, The additive B contains the ZSM-5 type zeolite in an amount of 25 to 60 mass %, The content ratio of phosphorus to alumina contained in the additive B is a molar ratio of P2O5 / Al2O3 of 0.20 to 0.30 when the phosphorus component is converted into P2O5, A mixed additive for a fluid catalytic cracking catalyst, comprising the additive A in an amount of 25 to 75 mass %. [4] A fluid catalytic cracking catalyst composition comprising a fluid catalytic cracking catalyst and either the additive for a fluid catalytic cracking catalyst according to claim 1 or the mixed additive for a fluid catalytic cracking catalyst according to claim 3. [Effects of the Invention]

[0013] The additive for a fluid catalytic cracking catalyst according to the present invention makes it possible to obtain lower olefins such as propylene in high yield from the initial stage to the final stage of the treatment process of a feed hydrocarbon oil. Furthermore, the fluid catalytic cracking catalyst additive according to the present invention makes it possible to obtain lower olefins such as propylene in high yield even when the feed hydrocarbon oil contains large amounts of heavy metals such as vanadium, nickel, etc. Furthermore, the method for producing a fluid catalytic cracking catalyst additive according to the present invention makes it possible to produce a fluid catalytic cracking catalyst additive that can obtain lower olefins such as propylene in high yield even when the feed hydrocarbon oil contains large amounts of heavy metals such as vanadium, nickel, etc. DETAILED DESCRIPTION OF THE INVENTION

[0014] [Additive for fluid catalytic cracking catalyst] The fluid catalytic cracking catalyst additive (FCC catalyst additive) according to the present invention is an additive for a fluid catalytic cracking catalyst comprising a pentasil-type zeolite and an inorganic oxide matrix component containing two types of phosphorus compounds, characterized in that the fluid catalytic cracking catalyst additive contains 25 to 60 mass% of the pentasil-type zeolite, the phosphorus content relative to the alumina contained in the fluid catalytic cracking catalyst additive is a molar ratio P2O5 / Al2O3 of 0.30 to 0.53 when the phosphorus component is converted into P2O5, the molar ratio SiO2 / Al2O3 of the silicon dioxide content relative to the alumina contained in the pentasil-type zeolite is 25 to 40, and the attrition resistance index (CAI) is 20 or less. The FCC catalyst additive according to the present invention will be described in detail below.

[0015] The FCC catalyst additive of the present invention comprises a pentasil-type zeolite and an inorganic oxide matrix component containing two phosphorus compounds. The pentasil-type zeolite is dispersed in the inorganic oxide matrix component. Examples of pentasil-type zeolites include ZSM-5, ZSM-11, ZSM-12, ZSM-22, ZSM-23, ZSM-35, ZSM-38, and ZSM-48. Among these pentasil-type zeolites, ZSM-5 is particularly preferred because it has a solid acid with high acid strength and exhibits high shape selectivity, thereby significantly increasing the octane number of gasoline and the yield of light olefins.

[0016] The FCC catalyst additive according to the present invention contains 25 to 60 mass% of pentasil-type zeolite in the fluid catalytic cracking catalyst additive. From the viewpoint of increasing the yield of lower olefins such as propylene, the content of the pentasil-type zeolite in the fluid catalytic cracking catalyst additive is preferably 25 mass% or more, and more preferably 30 mass% or more. On the other hand, from the viewpoint of not reducing the production amount of the target lower olefins due to overcracking of the feed hydrocarbon oil and from the viewpoint of maintaining physical properties within a practically usable range, such as moldability and abrasion resistance of the FCC catalyst additive, the content of the pentasil-type zeolite in the fluid catalytic cracking catalyst additive is preferably 60 mass% or less, and more preferably 50 mass% or less.

[0017] The FCC catalyst additive according to the present invention has a molar ratio of SiO2 / Al2O3, which is the ratio of silicon dioxide to alumina contained in the pentasil-type zeolite, of 25 to 40. The ratio of silicon to aluminum contained in the pentasil-type zeolite constituting the FCC catalyst additive according to the present invention, converted into the mass ratio of SiO2 to Al2O3 (mass of SiO2 / mass of Al2O3), is preferably 25 to 40. A mass ratio of SiO2 to Al2O3 of 25 or more is preferred because the acid density on the pentasil-type zeolite is not too high, preventing over-cracking of the feed hydrocarbon oil and increasing the yield of the desired lower olefins such as propylene. On the other hand, a mass ratio of SiO2 to Al2O3 of 40 or less is preferred because the acid density on the pentasil-type zeolite is appropriate and the cracking activity of the FCC catalyst additive for the feed hydrocarbon oil is excellent.

[0018] The primary particle diameter of the pentasil-type zeolite is preferably 0.3 to 5 μm. The primary particle diameter of the pentasil-type zeolite is the median diameter (D50) measured by the method employed in the examples described later. The primary particle diameter of the pentasil-type zeolite is preferably 0.3 to 5 μm. A primary particle diameter of the pentasil-type zeolite of 0.3 μm or more is preferable because it can prevent a decrease in the hydrothermal resistance of the FCC catalyst additive and a decrease in the yield of light olefins. Furthermore, a primary particle diameter of the pentasil-type zeolite of 0.3 μm or more is preferable because it increases the voids between the pentasil-type zeolite particles in the FCC catalyst additive, reducing the bulk density (ABD) of the FCC catalyst additive and preventing deterioration of the attrition of the FCC catalyst additive.

[0019] The primary particle size of the pentasil-type zeolite is preferably 5 μm or less from the viewpoint of preventing a decrease in catalytic activity due to a decrease in dispersibility of the reaction field caused by the solid acid or pores of the zeolite within the particles of the FCC catalyst additive.

[0020] The FCC catalyst additive of the present invention includes an inorganic oxide matrix component containing two phosphorus compounds. The inorganic oxide matrix component containing two phosphorus compounds includes a binder that binds the components in the FCC catalyst additive, and this binder is made of a phosphorus-containing oxide, preferably an oxide containing phosphorus and aluminum. The phosphorus species derived from aluminum phosphate, which is one of the two phosphorus compounds contained in the inorganic oxide matrix, mainly functions as a binder, while the phosphoric acid-derived phosphorus species functions to modify the aluminum in the zeolite.

[0021] As the phosphorus component, orthophosphoric acid (hereinafter also simply referred to as "phosphoric acid"), ammonium dihydrogen phosphate, diammonium hydrogen phosphate, trimetaphosphoric acid, pyrophosphoric acid, tripolyphosphoric acid, and the like are preferred.

[0022] The amount of phosphorus in the FCC catalyst additive, converted to the amount of diphosphorus pentoxide (PO), is 5% by mass or more, preferably 7% by mass or more. The amount of phosphorus can be measured by ICP atomic emission spectroscopy under the conditions employed in the examples described below. When the amount of phosphorus is within this range, the FCC catalyst additive has excellent abrasion resistance because the binder has a strong bonding force between the pentasil-type zeolite, the alumina component, and the extender such as kaolin. Furthermore, the hydrothermal stability of the pentasil-type zeolite is maintained, which is preferable because it can increase the yield of lower olefins such as propylene in the catalytic cracking of the feed hydrocarbon oil.

[0023] The amount of phosphorus is 20% by mass or less, preferably 15% by mass or less, based on the above criteria. When the amount of phosphorus is within this range, the pore volume of the FCC catalyst additive is not too small, allowing the reactants to diffuse within the pores, and thus increasing the yield of lower olefins such as propylene in the catalytic cracking of the feed hydrocarbon oil.

[0024] The phosphorus content relative to alumina contained in the FCC catalyst additive is preferably a molar ratio of P2O5 / Al2O3 of 0.30 to 0.53, more preferably 0.33 to 0.50, calculated as P2O5. A molar ratio of P2O5 / Al2O3 of 0.30 or more is preferred because it improves the hydrothermal resistance of the additive, and a molar ratio of 0.53 or less is preferred because it provides excellent wear resistance.

[0025] The amount of the optional binder contained in the FCC catalyst additive is preferably 5 to 25 mass %, more preferably 10 to 15 mass %.

[0026] The inorganic oxide matrix component may also contain an inorganic oxide extender typically incorporated into FCC catalyst additives. Examples of extenders include clay minerals such as kaolin, bentonite, and halloysite, with kaolin being particularly preferred. The extender may also be a heat-treated product of one of these clay minerals. The amount of extender contained in the FCC catalyst additive is the amount of the FCC catalyst additive minus the total amount of the pentasil zeolite, binder, and alumina component.

[0027] The pore volume of the FCC catalyst additive according to the present invention in the pore diameter range of 2 to 50 nm, as measured by the BJH method, is preferably 0.03 ml / g or more, and the upper limit may be, for example, 0.08 ml / g. When the pore volume is within this range, lower olefins such as propylene can be obtained in high yield in FCC even when the feed hydrocarbon oil contains large amounts of heavy metals such as vanadium and nickel.

[0028] The FCC catalyst additive according to the present invention typically has a microspherical particle shape. Since the FCC catalyst additive can be used by mixing with an FCC catalyst containing faujasite-type zeolite intended for gasoline production in an FCC unit, the particle size of the FCC catalyst additive is preferably comparable to or larger than that of a typical FCC catalyst. The average particle size of the microspherical particles constituting the FCC catalyst additive, as measured by laser diffraction / scattering under the conditions employed in the examples described below, is preferably 40 to 140 μm, more preferably 60 to 120 μm.

[0029] [Method for producing additives for fluid catalytic cracking catalysts] The method for producing an additive for a fluid catalytic cracking catalyst according to the present invention is a method for producing an additive for a fluid catalytic cracking catalyst comprising a pentasil-type zeolite and an inorganic oxide matrix component containing two types of phosphorus compounds, the method comprising: Step a: obtaining a mixed slurry containing a pentasil-type zeolite and an inorganic oxide matrix component containing two kinds of phosphorus compounds; Step b: spray-drying the mixed slurry to obtain a dry additive; and step c: heat treating the dried additive to obtain an additive for a fluid catalytic cracking catalyst. Hereinafter, each step included in the method for producing an additive for a fluid catalytic cracking catalyst (method for producing an additive for an FCC catalyst) according to the present invention will be described.

[0030] (Step a: Step of obtaining mixed slurry) The method for producing an FCC catalyst additive according to the present invention comprises the steps of: (a) obtaining a mixed slurry containing a pentasil-type zeolite and an inorganic oxide matrix component containing two phosphorus compounds. Specific and preferred embodiments of the pentasil-type zeolite contained in the mixed slurry in the step (a) are as described above.

[0031] In the method for producing an FCC catalyst additive according to the present invention, a pentasil-type zeolite and an inorganic oxide matrix component containing two phosphorus compounds are mixed to prepare a slurry. The inorganic oxide matrix component may contain a binder material consisting of an oxide containing phosphorus or an oxide containing phosphorus and aluminum, an extender, a dispersion medium, and, if necessary, an optional binder material. The optional binder may include inorganic oxides such as silica, silica-magnesia, titania, zirconia, silica-zirconia, and calcium silicate.

[0032] The mixed slurry can be prepared by a conventional method. The solid content of the mixed slurry is preferably about 25 to 60 mass % from the viewpoint of the operation of spray drying the mixed slurry carried out in the step b described below.

[0033] That is, the amount of pentasil-type zeolite contained in the mixed slurry is preferably 25% by mass or more, and preferably 30% by mass or more, from the viewpoint of obtaining an FCC catalyst additive that produces a high yield of lower olefins such as propylene. On the other hand, the amount of pentasil-type zeolite contained in the mixed slurry is preferably 60% by mass or less, and preferably 50% by mass or less, from the viewpoint of obtaining an FCC catalyst additive without reducing the target amount of lower olefins produced by overcracking the feed hydrocarbon oil. The amount of pentasil-type zeolite contained in the mixed slurry is defined as the mass % concentration of pentasil-type zeolite relative to the mass of solids other than the dispersion medium that make up the mixed slurry.

[0034] The inorganic oxide matrix component containing two phosphorus compounds contains a binder material for binding the components in the FCC catalyst additive. This binder material is made of an oxide containing phosphorus or an oxide containing phosphorus and aluminum. The phosphorus-containing oxide is a material that can be converted into phosphate ions (PO4 3- ) is preferred. Examples of oxides containing phosphorus and aluminum include compounds such as aluminum dihydrogen phosphate (Al(H2PO4)3), aluminum hydrogen phosphate (Al2(HPO4)3), and aluminum phosphate (AlPO4). Among these compounds, aluminum dihydrogen phosphate (Al(H2PO4)3) is preferred from the viewpoints of its ability to harden and bond each component in the FCC catalyst additive and its high reactivity with zeolite.

[0035] These compounds may be used alone or in combination of two or more. The phosphorus-containing binder raw material preferably contains aluminum dihydrogen phosphate as the main component (a component accounting for 70% by mass or more).

[0036] An aqueous solution of phosphorus may be used as a binder raw material containing phosphorus. Commercially available aqueous solutions include aluminum dihydrogen phosphate (Al(H2PO4)3) aqueous solutions (brands: 50L, 100L, Acidophos 120M, manufactured by Taki Chemical Co., Ltd.).

[0037] The phosphorus-containing binder raw material is used in an amount such that the phosphorus content is 5 to 20 mass %, preferably 6 to 15 mass %, calculated as diphosphorus pentoxide (PO) (where the total amount of the slurry components other than the dispersion medium is taken as 100 mass %). A phosphorus content of 5 mass % or more is preferred because it provides excellent wear resistance and allows the production of an FCC catalyst additive that can produce lower olefins such as propylene in high yields in the catalytic cracking of feed hydrocarbon oil. On the other hand, a phosphorus content of 15 mass % or less is preferred because it prevents a significant decrease in initial activity and provides excellent wear resistance.

[0038] As the phosphorus component, orthophosphoric acid (hereinafter also simply referred to as "phosphoric acid"), ammonium dihydrogen phosphate, diammonium hydrogen phosphate, trimetaphosphoric acid, pyrophosphoric acid, tripolyphosphoric acid, and the like are preferred.

[0039] (Step b: Step of obtaining dry additive) Next, the method for producing an FCC catalyst additive according to the present invention includes step b: spray-drying the mixed slurry to obtain a dried additive. Step b is a step of spray-drying the mixed slurry obtained in step a. The dried additive can be obtained by spray-drying the mixed slurry. In step b, the dried additive may be pulverized to obtain a powder of the dried additive. The spray-drying of the mixed slurry can be carried out by a known method using a spray dryer.

[0040] In the step b, the mixed slurry is spray-dried under the following conditions, for example. Spray inlet temperature: 200~450℃ ·Spray dryer outlet temperature: 110~350℃

[0041] Thereafter, the powder of the dried additive obtained by spray drying the mixed slurry is allowed to cool to room temperature (for example, 0 to 40°C). After the powder of the dried additive has cooled, the powder is classified to adjust the average particle size to, for example, 40 to 140 μm, preferably 60 to 120 μm.

[0042] (Step c: Step of obtaining additives for fluid catalytic cracking catalyst) Next, the method for producing an FCC catalyst additive according to the present invention includes step c: heat-treating the dried additive to obtain an additive for a fluid catalytic cracking catalyst. Step c is a step of heat-treating the dried additive obtained in step b at a temperature of 500 to 750°C, preferably 550 to 700°C, for preferably 0.2 to 5.0 hours, more preferably 0.5 to 2.0 hours. In step c, the additive for an FCC catalyst can be obtained by heat-treating the dried additive.

[0043] When the dry additive is pulverized, the powder of the dry additive is heated at a heating rate of 150°C / hour or more, preferably 180°C / hour or more. A heating rate of less than 150°C / hour is undesirable because the reaction between the alumina component and the phosphorus-containing binder raw material proceeds excessively, and the yield of lower olefins such as propylene may decrease due to heavy metal poisoning of the FCC catalyst additive. The upper limit of the heating rate may be, for example, 800°C / hour, although this depends on the heating apparatus.

[0044] The heat treatment is preferably carried out in a water vapor atmosphere from the viewpoints of further diffusing the phosphorus-containing binder raw material, promoting the modification of the zeolite acid sites, and further suppressing the blocking of the zeolite pores by polyphosphoric acid.

[0045] [Fluid catalytic cracking catalyst composition] The fluid catalytic cracking catalyst composition according to the present invention is a catalyst composition comprising a fluid catalytic cracking catalyst (FCC catalyst) and either one of the above-mentioned additive for fluid catalytic cracking catalysts (FCC catalyst additives) and a mixed additive for fluid catalytic cracking catalysts described below. That is, the fluid catalytic cracking catalyst composition according to the present invention is proposed as a catalyst composition comprising the above-mentioned additive for FCC catalysts (hereinafter also referred to as "additive catalyst") mixed with an FCC catalyst containing faujasite zeolite used in the fluid catalytic cracking of feed hydrocarbon oil in an FCC unit, as an application of the additive for FCC catalysts.

[0046] As the FCC catalyst containing faujasite-type zeolite, a conventional FCC catalyst used in an FCC unit can be used, such as commercially available FCC catalysts such as DCT, ACZ, and CVZ (all of which are trademarks or registered trademarks of products manufactured by JGC Catalysts and Chemicals Co., Ltd.).

[0047] The amount of the FCC catalyst additive is preferably 0.1% by mass or more, more preferably 1% by mass or more, when the total amount of the FCC catalyst additive and the FCC catalyst is taken as 100% by mass, from the viewpoint of obtaining lower olefins such as propylene in high yield even when the feed hydrocarbon oil contains a large amount of heavy metals in FCC. On the other hand, from the viewpoint of cracking activity of the feed hydrocarbon oil, the amount of the FCC catalyst additive used is generally 30% by mass or less, but may be added up to 60% by mass in new processes for increasing the production of light olefins, etc.

[0048] As the FCC catalyst additive, the FCC catalyst additive of the present invention may be used alone, or a mixed FCC catalyst additive containing other FCC catalyst additives may be used.

[0049] The mixed additive for a fluid catalytic cracking catalyst according to the present invention is a mixed additive for a fluid catalytic cracking catalyst comprising additive A and additive B. Additive A contained in the mixed additive for a fluid catalytic cracking catalyst according to the present invention is the above-mentioned additive for a fluid catalytic cracking catalyst. Additive B comprises ZSM-5 type zeolite and the above-mentioned inorganic oxide matrix component. Additive B contains 25 to 60 mass% of ZSM-5 type zeolite in additive B. The phosphorus content relative to alumina contained in additive B is a molar ratio of P2O5 / Al2O3 of 0.20 to 0.30 when the phosphorus component is converted into P2O5. Furthermore, the mixed additive for a fluid catalytic cracking catalyst contains 25 to 75 mass% of additive A.

[0050] Although the additive A contained in the mixed additive for a fluid catalytic cracking catalyst according to the present invention does not have high initial catalytic activity, it can maintain high catalytic activity after steaming. In contrast, Additive B has high initial catalytic activity, but its catalytic activity decreases after steaming. Therefore, when either additive is used in an FCC unit, the catalytic activity is likely to change from the beginning to the end of the feed hydrocarbon oil treatment process, making it impossible to maintain stable catalytic activity. As a result, it becomes necessary to timely adjust the amount of additive added, etc., to maintain stable catalytic activity from the beginning to the end of the feed hydrocarbon oil treatment process. From this perspective, the fluid catalytic cracking catalyst additive mixture of the present invention, by mixing Additive A and Additive B in a predetermined ratio, can maintain stable catalytic activity for a certain period from the beginning, while reducing the frequency of adjusting conditions such as the amount and timing of addition of the additive.

[0051] The mixed additive for a fluid catalytic cracking catalyst according to the present invention is a mixed additive containing different types of mixed additives for a fluid catalytic cracking catalyst. The mixed additive for a fluid catalytic cracking catalyst according to the present invention is technically characterized in that one of the additives for a fluid catalytic cracking catalyst, additive B, uses ZSM-5 zeolite as the pentasil zeolite, and further the phosphorus content relative to alumina contained in additive B is a molar ratio of P2O5 / Al2O3 of 0.20 to 0.30 when the phosphorus component is converted into P2O5.

[0052] In the fluid catalytic cracking process of feedstock hydrocarbon oil in which the FCC catalyst additive or mixed additive for fluid catalytic cracking catalyst according to the present invention is used, the fluid catalytic cracking conditions of hydrocarbon oil in a conventional FCC unit can be adopted, except that the FCC catalyst additive according to the present invention is used as the FCC catalyst additive. [Example]

[0053] The present invention will be specifically explained below with reference to examples, but the present invention is not limited to these examples in any way.

[0054] [Methods for measuring or evaluating additives for FCC catalysts] The measurement methods and evaluation test methods for FCC catalyst additives in the examples are as follows.

[0055] (Method for measuring the content of each element) Mass analysis of each element contained in the FCC catalyst additive was performed using an atomic absorption spectrophotometer for Na and an inductively coupled plasma spectrometer for elements other than Na. Specifically, sulfuric acid and hydrofluoric acid were added to zeolite (ZSM-5) or the catalyst, heated, and evaporated to dryness. The dried residue was dissolved in concentrated hydrochloric acid and diluted with water to a concentration of 10 to 100 ppm by mass to prepare a measurement solution. The prepared measurement solution was then analyzed using an atomic absorption spectrophotometer (Z-2310) manufactured by Hitachi High-Tech Science Corporation and an inductively coupled plasma spectrometer (ICPS-8100) manufactured by Shimadzu Corporation.

[0056] (Average particle size of FCC catalyst additives and catalysts) The particle size distribution of the sample was measured using a laser diffraction / scattering particle size analyzer (LA-300) manufactured by Horiba, Ltd. Specifically, the sample was placed in a solvent (water) so that the light transmittance was in the range of 70-95%, and measurements were performed under the following conditions: circulation rate: 2.8 L / min, ultrasonic irradiation: 3 minutes, repetition number: 30 times. The median diameter (D50) was used as the average particle size.

[0057] (Specific surface area and pore volume of additives for FCC catalysts) Measurements of the specific surface area (SA) and pore volume of pores with a diameter of 50 nm or less were performed using a Microtrac-Bell Corporation BELSORP-mini Ver. 2.5.6. Specifically, measurements were performed using samples pretreated at 500°C for 1 hour, with nitrogen as the adsorbed gas. The specific surface area (SA) of the FCC catalyst additive was calculated using the BET method, the volume of micropores with a pore diameter of 2 nm or less was calculated using the MP method, and the volume of mesopores with a pore diameter of 2 to 50 nm was calculated using the BJH method.

[0058] (Abrasion Resistance Index; CAI) The attrition index (CAI) is a value measured by the method described in Catalysts and Chemicals Technical Report, Vol. 13, No. 1, p. 65, 1966 (Non-Patent Document 1). The attrition index (CAI) of an FCC catalyst additive was measured by the method described in the above non-patent document. Note that the higher the attrition index (CAI), the more likely the catalyst is to powder during use.

[0059] (bulk density; ABD) The bulk density (ABD) was calculated from the volume and mass of the prepared catalyst sample, which was calcined at 600°C for 2 hours in the air, cooled, and then placed in a measuring cylinder without vibration.

[0060] [Example 1] Additive preparation 1 990 g of ZSM-5 zeolite powder (SiO2 / Al2O3 ratio = 37.6, solids concentration: 97 wt%) and 1287 g of kaolin (Al2O3 concentration: 36.5 wt%) were suspended in 4000 g of ion-exchanged water and stirred thoroughly. After stirring, 723 g of an aqueous solution of aluminum phosphate monobasic (P2O5 concentration: 33.0 wt%, Al2O3 concentration: 8.5 wt%) and 117 g of an aqueous solution of phosphoric acid (P2O5 concentration: 61.6 wt%) were added and stirred thoroughly to obtain a blended slurry. The resulting blended slurry was spray-dried in a spray dryer at an inlet temperature of 240 °C and an outlet temperature of 135 °C to obtain a spray-dried powder with an average particle size of 80 μm. The resulting spray-dried powder was calcined in a muffle furnace at 600 °C for 1 hour to obtain Additive 1, an additive for FCC catalysts.

[0061] [Example 2] Additive preparation 2 Additive 2 was obtained in the same manner as in Example 1, except that 990 g of ZSM-5 zeolite powder (SiO / AlO ratio = 37.6, solid content concentration: 97%) and 1243 g of kaolin (AlO concentration: 36.5 mass%) were suspended in 4000 g of ion-exchanged water and thoroughly stirred, and then 723 g of an aqueous solution of aluminum phosphate monobasic (PO concentration: 33.0 mass%, AlO concentration: 8.5 mass%) and 175 g of an aqueous solution of phosphoric acid (PO concentration: 61.6 mass%) were added and thoroughly stirred to obtain a blended slurry.

[0062] [Example 3] Additive preparation 3 Additive 3 was obtained in the same manner as in Example 1, except that 990 g of ZSM-5 zeolite powder (SiO / AlO ratio = 37.6, solid content concentration: 97 mass%) and 1200 g of kaolin (AlO concentration: 36.5 mass%) were suspended in 4000 g of ion-exchanged water and thoroughly stirred, and then 723 g of an aqueous solution of aluminum phosphate monobasic (PO concentration: 33.0 mass%, AlO concentration: 8.5 mass%) and 234 g of an aqueous solution of phosphoric acid (PO concentration: 61.6 mass%) were added and thoroughly stirred to obtain a blended slurry.

[0063] [Comparative Example 1] Additive preparation R1 Additive R1 was obtained in the same manner as in Example 1, except that 990 g of ZSM-5 zeolite powder (SiO / AlO ratio = 37.6, solid content concentration: 97 mass%) and 1373 g of kaolin (AlO concentration: 36.5 mass%) were suspended in 4000 g of ion-exchanged water and thoroughly stirred, and then 723 g of an aqueous solution of aluminum phosphate monobasic (PO concentration: 33.0 mass%, AlO concentration: 8.5 mass%) was added and thoroughly stirred to obtain a blended slurry.

[0064] Comparative Example 2 Additive preparation R2 Additive R2 was obtained in the same manner as in Example 1, except that 990 g of ZSM-5 zeolite powder (SiO / AlO ratio = 37.6, solid content concentration: 97 mass%) and 1157 g of kaolin (AlO concentration: 36.5 mass%) were suspended in 4000 g of ion-exchanged water and thoroughly stirred, and then 723 g of an aqueous solution of aluminum phosphate monobasic (PO concentration: 33.0 mass%, AlO concentration: 8.5 mass%) and 292 g of an aqueous solution of phosphoric acid (PO concentration: 61.6 mass%) were added and thoroughly stirred to obtain a blended slurry.

[0065] Table 1 shows the chemical compositions and physical properties of FCC catalyst additives 1 to 3 prepared in Examples 1 to 3, respectively, and FCC catalyst additives R1 and R2 prepared in Comparative Examples 1 and 2, respectively.

[0066] [Table 1]

[0067] (Catalyst performance) FCC catalyst additives 1 to 3 and FCC catalyst additives R1 and R2 produced in Examples 1 to 3, respectively, were subjected to catalytic evaluation tests using an ACE-MAT (Advanced Cracking Evaluation - Micro Activity Test) under the same feedstock and the same reaction conditions. Prior to the catalytic evaluation tests, each FCC catalyst additive or an additive composition combining each FCC catalyst additive was calcined at 600°C in air for 2 hours, and then pretreated at 810°C for 13 hours and 60 hours in a 100% steam atmosphere.

[0068] A mixed catalyst was prepared by blending an FCC catalyst additive pretreated with an FCC equilibrium catalyst (CVZ catalyst manufactured by JGC Catalysts and Chemicals Co., Ltd.) so that the amount of the FCC catalyst additive or additive composition in the mixed catalyst was a constant amount of 2.4 wt %, and the mixed catalyst was evaluated (measurement of propylene yield (mass%)) using an ACE-MAT activity tester. In Example 4, a blend of Additive 2 and Additive R1 was used as the additive composition, and in Comparative Example 3, a blend of Additive R1 and Additive R2 was used as the additive composition.

[0069] The reaction conditions were as follows: Reaction temperature: 510℃ Feedstock: 100% desulfurized vacuum gas oil (DSVGO) WHSV:8h -1 ·Catalyst / oil ratio: 5% by mass / 1% by mass Table 2 shows the evaluation results of the mixed catalyst containing the FCC catalyst additive.

[0070] [Table 2]

[0071] [FCC catalyst additive activity evaluation results] As shown in Table 2, the catalyst activity evaluation results revealed that the FCC catalyst compositions containing the FCC catalyst additives prepared in Examples 1 to 4 were superior in terms of high propylene yield (yield) compared to the FCC catalyst compositions prepared in Comparative Examples 1 to 3. [Industrial Applicability]

[0072] As described above, the additive for a fluid catalytic cracking catalyst according to the present invention is suitable for producing lower olefins such as propylene in high yield from the initial to final stages of the treatment process of a feed hydrocarbon oil, and is therefore industrially useful.

Claims

1. An inorganic oxide matrix component containing a pentasil type zeolite and two types of phosphorus compounds; An additive for a fluid catalytic cracking catalyst comprising: The fluid catalytic cracking catalyst additive contains the pentasil type zeolite in an amount of 25 to 60 mass %, The molar ratio of phosphorus and aluminum oxide (P 2 O 5 / Al 2 O 3 ) is 0.30 to 0.53; The molar ratio of silicon and aluminum contained in the pentasil-type zeolite in terms of oxide (SiO 2 / Al 2 O 3 ) is 25 to 40; An additive for a fluid catalytic cracking catalyst having an attrition index (CAI) of 20 or less.

2. A process for obtaining a dry additive by spray-drying a mixed slurry containing a pentasil-type zeolite and an inorganic oxide matrix component containing two kinds of phosphorus compounds; and heat treating the dried additive at 500 to 750° C. to obtain an additive for a fluid catalytic cracking catalyst. The solid content of the mixed slurry contains 25 to 60% by weight of pentasil type zeolite, The solid content of the mixed slurry contains phosphorus in an amount of 5 to 20 mass% calculated as diphosphorus pentoxide, The molar ratio of silicon to aluminum contained in the pentasil-type zeolite (SiO 2 / Al 2 O 3 ) calculated as oxides is 25 to 40.

3. The additive for a fluid catalytic cracking catalyst according to claim 1, and additive B consisting of an inorganic oxide matrix component containing one phosphorus compound and a ZSM-5 type zeolite; The additive B contains 25 to 60 mass % of the ZSM-5 type zeolite, The molar ratio of phosphorus and aluminum contained in the additive B in terms of oxide (P 2 O 5 / Al 2 O 3 ) is 0.20 to 0.30, A mixed additive for a fluid catalytic cracking catalyst comprising the additive for a fluid catalytic cracking catalyst in an amount of 25 to 75 mass %.

4. A fluid catalytic cracking catalyst composition comprising a fluid catalytic cracking catalyst and either the additive for a fluid catalytic cracking catalyst according to claim 1 or the mixed additive for a fluid catalytic cracking catalyst according to claim 3.